Knowledge sharing and knowledge protection in inter-organizational collaboration: uncovering the underlying relationships that influence innovation - Oliveira, Mírian (2020)
This research addresses the sources of absorptive capacity that influence innovation considering the dynamics of knowledge, since the balance between knowledge protection and inter-organizational knowledge sharing may enhance innovation. We examine the literature that suggests organizational absorptive capacity plays a significant role in achieving innovation. This research in progress proposes two alternative research models based on following constructs knowledge protection, interorganizational knowledge sharing, potential absorptive capacity, realized absorptive capacity and innovation. This original contribution seeks to expand the recent literature on knowledge protection specifically at the inter-organizational level. Both models can be used to deliver relevant contributions on either the mediating or moderating influence of knowledge protection. The theoretical contributions illustrate a) the mediating role of inter-organizational knowledge sharing between the potential and realized absorptive capacity, and b) clarify the influence knowledge protection has on interorganizational knowledge sharing, and the potential and the realized absorptive capacity. Furthermore, the empirical findings are expected to a) show managers how inter-organizational knowledge sharing mediates the potential and realized absorptive capacity, thus enabling innovation, and b) alert managers to the possible negative influence of knowledge protection on absorptive capability, interorganizational knowledge sharing and innovation.